An Innovative Communication Paradigm for the Future of Public Relations: Artificial Intelligence - Ümmü Özlem Çerçi (Türkiye İletişim Araştırmaları Dergisi)
This article examines the role of artificial intelligence, an innovative communication paradigm for the future of public relations. Artificial intelligence stands out as a factor that leads to significant changes and transformations in the communications industry. This article extensively examines how artificial intelligence, utilized to optimize information processing, data analysis, and decision-making processes, can have a transformative impact within the field of public relations. The article focuses on how artificial intelligence changes and improves public relations practices in areas such as media monitoring, crisis management, reputation management, customer relationship management and content production. It also focuses on the potential of AI to help develop better targeting and communication strategies, with particular emphasis on its data analysis and predictive capabilities. This article provides a comprehensive evaluation that will help public relations professionals, businesses and communications industry stakeholders understand the potential of artificial intelligence technology. It also addresses future communications trends and current and potential questions regarding the ethical dimension of artificial intelligence, offering guidance on how public relations can be integrated with this innovative technology.